PENGARUH PERILAKU KEPEMIMPINAN KEPALA SEKOLAH DAN KOMPETENSI GURU TERHADAP KINERJA GURU SEKOLAH DASAR DI KELURAHAN TALANG BETUTU - Kiki Retnowati; Nur Ahyani; Syaiful Eddy (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The purpose of this study is to determine if teacher competency and principal leadership have a meaningful impact on the performance of teachers in state elementary schools in Talang Betutu Subdistrict. Multiple regression analysis techniques and quantitative methods are used in this study. In Talang Betutu Village, there are four state elementary schools with 114 teachers. The data was gathered using a Likert scale. In this study, random sampling was the sample technique. IBM SPSS version 26 was then used to tabulate and analyze the data. With a value of 11.627 or > 3.077 and p = 0.000 (p<0.05), the research findings demonstrated a positive and significant relationship between leader leadership and teacher competence on the level of teacher performance. Teacher competency and the principal's leadership both positively impact teacher performance by 49.3% at the same time, with other factors influencing the remaining 50.7%.